TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) DI AIR DINGIN KOTA PADANG DALAM KARYA LUKIS POST IMPRESIONIS - Maysandy Haryady; Yasrul Sami; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize Air Dingin landfill in the city of Padang in post  impressionist painting. Displays the state of landfills and activities that take place, as an effort to socialize and inform about waste, waste utilization, and landfills. The method and process of the works used in the creation of this painting go through several stages: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Completion. This work describes some state of Air Dingin landfills as; existing facilities, disposal process, and life activities that are there. As for the work discussed, it consists of ten post impressionist style paintings with the title: suasana pagi di jalur masuk, antrian pembuangan, proses pembongkaran, ma alauan jawi pulang, kolam lindi, marawok, pulang marawok, tenda pemulung, bangau putih, alat berat.Kata kunci : Sampah, tempat pembuangan akhir sampah, pengelolaan sampah, senilukis.